Pengaruh Partisipasi Penyusunan Anggaran dan Motivasi Kerja Terhadap Kinerja Manajerial dengan Gaya Kepemimpinan sebagai Variabel Moderating - Eva Hidayati Safitri; Djoko Kristianto (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The Karanganyar Regency Government functions as an autonomous region comprising various work units, including offices, agencies, and departments. This study aims to examine the influence of budget participation and work motivation on managerial performance, and to analyze the moderating role of leadership style within this relationship in the Regional Government Work Units (SKPD) of Karanganyar Regency. This research employed a quantitative approach, utilizing primary data as its main source. The study population consisted of all 8,019 employees across the SKPD in Karanganyar Regency. A purposive sampling technique was used to select 100 employee respondents. The findings indicate that Budget Participation has a positive but not statistically significant effect on managerial performance. Conversely, the Work Motivation variable demonstrates a positive and statistically significant influence on the managerial performance of SKPD in Karanganyar Regency. Furthermore, Leadership Style was found to moderate the effects of both Budget Participation and Work Motivation on Managerial Performance. This suggests that an improved leadership style can enhance the effectiveness of budget participation and work motivation in boosting managerial performance within the SKPD of Karanganyar Regency